PENGARUH PENGGUNAAN MEDIA AUDIO TERHADAP KETERAMPILAN MENYIMAK PESERTA DIDIK DI KELAS V SEKOLAH DASAR MUHAMMADIYAH 2 PONTIANAK - Neti Suratmi; Marzuki Marzuki; Siti Halidjah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractThe problem in this thesis is "Is there any influence of audio media on listening skill of students in fifth class Muhammadiyah 2 Pontianak primary school?".Aims to analyze how much influence the use of audio media on the skills of listening learners in fifth class Primary School. The research method used is experimental method. The research used quasi experimental with nonequivalent control group design.The population in this study were all students of fifth class, which amounted to 128 people, The sample in this study are students of fifth class  A and fifth class  B which numbered to 64 people. Data collection techniques used are measurement techniques and documentary studies. Data collection tool used in the form of test and photo documentation. Based on the data analysis, the average listening skill of the students in the control class is 75.65 and the average listening skill in the experimental class is 81.14. The t-test results show that there are different listening skills between learners who are taught using audio media and learners who taught without using audio media. (t_count= 1.65; significant level = 5%; dk = 62). Results effect size of this study amount to 0.375 (medium category). That is, the audio media affect the skills of listening learners in the fifth class  Muhammadiyah 2 Pontianak Elementary School.        Keywords: Influence, Audio Media, Listening Skill